2009
DOI: 10.1021/jm900716v
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy to Minimize Reactive Metabolite Formation: Discovery of (S)-4-(1-Cyclopropyl-2-methoxyethyl)-6-[6-(difluoromethoxy)-2,5-dimethylpyridin-3-ylamino]-5-oxo-4,5-dihydropyrazine-2-carbonitrile as a Potent, Orally Bioavailable Corticotropin-Releasing Factor-1 Receptor Antagonist

Abstract: Detailed metabolic characterization of 8, an earlier lead pyrazinone-based corticotropin-releasing factor-1 (CRF(1)) receptor antagonist, revealed that this compound formed significant levels of reactive metabolites, as measured by in vivo and in vitro biotransformation studies. This was of particular concern due to the body of evidence suggesting that reactive metabolites may be involved in idiosyncratic drug reactions. Further optimization of the structure-activity relationships and in vivo properties of pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 47 publications
0
44
0
Order By: Relevance
“…While the pyrolysis of sodium chlorodifluoroacetate requires elevated temperatures to generate the difluorocarbene, the pyrolysis of 2‐(fluorosulfonyl) acetic acid26 can be achieved at much lower temperatures which can be advantageous in some circumstances. For example, in their work on CRF antagonists, BMS found that a 2‐difluoromethoxypyridine derivative could be generated from a nitropyridone at room temperature under basic conditions using 2‐(fluorosulfonyl) acetic acid or its silylated variant27 and occurred in excellent yield (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…While the pyrolysis of sodium chlorodifluoroacetate requires elevated temperatures to generate the difluorocarbene, the pyrolysis of 2‐(fluorosulfonyl) acetic acid26 can be achieved at much lower temperatures which can be advantageous in some circumstances. For example, in their work on CRF antagonists, BMS found that a 2‐difluoromethoxypyridine derivative could be generated from a nitropyridone at room temperature under basic conditions using 2‐(fluorosulfonyl) acetic acid or its silylated variant27 and occurred in excellent yield (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Replacement of the bridging nitrogen atom of an atypical antipsychotic clozapine with an oxygen atom in loxapine or with sulfur in quetiapine ( Figure 2) prevents bioactivation of the dibenzoxazepine moiety and results in a drug with improved safety profile (Uetrecht et al, 1997). Furthermore, examples where resolution of RM liability (while maintaining primary pharmacology and disposition attributes) occurred through rational medicinal chemistry design has been considered to be a success story have also been presented (Bavetsias et al, 2010;Cox et al, 2010;Crawford et al, 2012;Finlay et al, 2012;Hartz et al, 2009;Kalgutkar et al, 2010Kalgutkar et al, , 2011Kalgutkar et al, , 2013Sarabu et al, 2012;Subramanian et al, 2010;Zhang et al, 2008). For instance, fluorofelbamate was specifically designed to eliminate the RM liability of felbamate on the basis of its bioactivation mechanism ( Figure 3) (Roecklein et al, 2007).…”
Section: Interpretation Of a ''Positive Signal'' (Detection Of A Gsh mentioning
confidence: 99%
“…Furthermore, Hartz andc o-workers synthesized as eries of corticotropin-releasing factor-1 receptor antagonists (CRF 1 )with nanomolar potency, such as BMS-764459 (4,F igure 1). [5] The synthesis of pyrazinone-derived antithrombotic compounds was reported elsewhere. [6] An anti-inflammatory effect [7] in xylene [8] and carrageenan-inducede dema, [9] ab iologically significant property that may ameliorate the progression of neurodegeneratived isorders, have been attributed to some pyrazinonederived scaffolds.…”
Section: Introductionmentioning
confidence: 99%